Unveiling a Meaningful Form of Cypripedium × ventricosum Sw. (Cypripedioideae, Orchidaceae) from Changbai Mountain, China: Insights from Morphological, Molecular, and Plastome Analyses - Ying Li; Xi Lu; Shuang Li; Yue Sun; Yuze Shan; Shizhuo Wang; Nan Jiang; Yiting Xiao; Qi Wang; Jiahui Yu; Qingtao Cao; Sulei Wu; et al. (Plants)
A Cypripedium plant was discovered in Wangqing County, Changbai Mountain, Jilin Province. This newly discovered plant of Cypripedium not only inhabits the same natural habitat as Cypripedium calceolus L. and Cypripedium × ventricosum Sw. but also has a morphology intermediate between that of C. calceolus and C. × ventricosum. Its dorsal sepals, petals, and synsepal are similar to those of C. calceolus, while the color of its lip is intermediate between that of C. calceolus and C. × ventricosum. For the purpose of distinguishing the newly discovered plant of Cypripedium from other Cypripedium plants, we provisionally named it W1. To further verify the taxonomic status of W1, we introduced three identified forms of C. × ventricosum and conducted molecular biology analyses with W1, C. calceolus, and C. × ventricosum. The analyses further confirmed the relationship between W1 and C. × ventricosum, and the phylogenetic analysis of the nuclear region demonstrated a close relationship between W1 and C. calceolus. Collectively, the morphological and molecular evidence indicates that W1 is a product of the backcross between C. × ventricosum and C. calceolus. Although it shows morphological differences from typical C. × ventricosum, it can still be considered a form of C. × ventricosum. We further investigated the chloroplast genome of this form of C. × ventricosum and determined that its total genome length was 196,850 bp. The genome contains 132 genes, including 87 protein-coding genes, 37 tRNA genes, and 8 rRNA genes. By analyzing the phylogenetic position and chloroplast genome of the form of C. × ventricosum, this study clarified the relationships among Cypripedium taxa with similar morphological characteristics, laying a foundation for research on orchid evolution and species conservation.